How does bitter taste guide the utilization of medicinal plants in the semiarid region of Brazil? - Silva, Temóteo; Ferreira Júnior, Washington; Santos, Francisco Igor; Elias, Lerticia; De La Cruz, Marleny Prada; Albuquerque, Ulysses Paulino (Ethnobotany Research and Applications, 2024)
Background: In numerous cultures, taste plays a pivotal role in the selection of medicinal plants by humans. We investigated whether the bitter taste of plants, as perceived by people, influenced the selection of medicinal plants for treating specific ailments. Method: Using the free-listing technique, we documented local knowledge about medicinal plants across five communities within Catimbau National Park, Pernambuco, Brazil. Participants who were older than 18 years and consented to participate in the study shared insights about medicinal plants, therapeutic targets, and taste attributes. The relationship between a plant's taste and the body systems for which it is recommended was analyzed using the chi-square test. Results: A bitter taste was associated with treating specific diseases; addressing ailments of the digestive, respiratory, gastrointestinal, and urogenital systems; infectious and parasitic diseases; and injuries as well as general symptoms and signs. Among the taste attributes reported, bitterness was the most common trait (42.34%), followed by astringent (26.78%), sweet (8.04%), sour (1.84%), and other/not classified (21.24%). Conclusion: In our study, we discovered that bitter taste is intricately linked to the selection of medicinal plants for treating certain ailments. Our findings underscore the significance of bitterness as a crucial factor in identifying plants for disease treatment in the region. Keywords: Bitter Taste, Chemosensory Perception, Local Medical Systems